Effectiveness of advanced coating systems for mitigating blast effects on steel components - (:unkn) unknown (WIT PRESS/COMPUTATIONAL MECHANICS PUBLICATIONS, 2008)
The objective of this work is to study the effectiveness of an advanced coating material, polyurea, as a blast mitigation tool for steel components. The response of polyurea coated steel components under blast loading is studied using the explicit LS-DYNA code with appropriate loading time histories supplied using a computational fluid dynamics (CFD) code developed at Penn State University, PUMA2 (Parallel Unstructured Maritime Aerodynamics-2). Results presented from this ongoing research study are related to an application of polyurea. onto armor grade steel plates and an examination of resulting failure modes and governing design parameters. Failure modes examined herein consist of fracturing in the polyurea/steel composite structure. Effects of thicknesses and locations of the polyurea on the blast mitigation are also studied. Explanations of selected strain-rate dependent material models for the steel and polyurea are provided. CFD blast simulations using PUMA2 are described and validated. Results obtained from numerical studies completed to date show that bare steel plate experiences severe fracturing and fragmentation under prescribed blast loading while polyurea coated plates are able to sustain prescribed pressures without fully fracturing.
Keywords: polyurea; armor steel; blast; finite element; computational fluid dynamics; PENETRATION; BEHAVIOR; POLYUREA; IMPACT; PLATES